PENGARUH VARIASI EKSTRAK METANOL KULIT BUAH RAMBUTAN (NEPHELIUM LAPPACEUM L.) TERHADAP KESTABILAN FISIK KRIM ANTIOKSIDAN - Syamsidi, Armini (Natural Science: Journal of Science and Technology, 2014)
ABSTRACT A research on influence methanol extracts concentration of fruit peel rambutan (N. lappaceum L.), concerning physical stability of creams antioxidant had been done. This research aims to obtain an antioxidant cream formulation O/W type from rambutan fruit peel extracts and compares activity of the antioxidant cream with extract from fruit peel rambutan with using free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. A total of 500 grams of fruit rambutan peel extracted with 80% methanol by maceration method and then extract obtained made antioxidant cream O/W type with the variation of the concentration of extract 1%, 2%, and 3% to the total weight of the cream. Evaluation of physical stability of creams includes organoleptic testing, creaming, viscosity testing and drop size of dispersed phase inversion before and after the storage conditions during the 12-hour accelerated alternately at 5°C and as many as 10 cycles of 35°C. Organoleptic observations show no change in color and odor on the third-cream formula. The research was used a completely randomized design and the data obtained were analyzed statistically distinguished by ansira on the confidence level. Statistical analysis shows that the concentration of rambutan fruit peel extracts give significant effect on the viscosity cream before and after accelerated storage conditions, while the size of the drops dispersed showed no significant effect. In this study, showed that no phase of inversion and creaming from all of cream. Formulation of skin creams with methanol extract of the fruit rambutan 1% cream can be categorized as the most stable, continuing antioxidant activity test showed that the cream with a concentration of extract 12,359 ppm, which inhibits 50% of free radicals.